Pendampingan Pembuatan Pakan Ternak dari Limbah Jerami - Rosyad, Aftonur; Myaskur; Subekan (Universitas Pangeran Diponegoro Nganjuk, 2022)
This service aims to provide assistance to the community, in utilizing straw waste. By utilizing straw as animal feed, our next hope is to be able to increase the income of farmers in Prayungan village, because the time they have used to find grass, they can use it for farming, because fodder no longer needs to use grass, but has been replaced with straw. The impact of changes in the Prayungan village community following the holding of this training included: (i) The community no longer throws away straw which can clog sanitation, (ii) The community no longer burns straw which can cause pollution, (iii) Increased awareness of the Prayungan village community about the benefits of straw , (iv) Growing community enthusiasm in making fermented animal feed, and (v) There are groups of capable farmers and the community sharing about processing straw as fermented animal feed.